Análise da transição da tecnologia mediante as novas regras de privacidade e segurança de dados em empresas de Big Data no mercado de comunicação - Luz, Carolina Maito (2018)
Big Data has been increasingly used for strategic decisions in various industries. Organizations collect, store and extract data for statistical data, structured and strategically used in their business. The present dissertation analyzed Big Data in the communication market in Brazil, its current and future in relation to security and privacy. Data marketed to the communication market were quickly restructured, which led them to require technological configurations in the sector innovation system. The study monitoring the global process of data mapes - the GDPR (General Regulation of Data Protection). This study was based on the Sociotechnical Theory of Innovation to understand the innovation system of the sector, specific in the process of transition of technological actions in modern society. The research method used was the case study that adopted a qualitative approach, with a data collection that involved two big Big Data companies in the Communication market. The results were the companies that need to be prepared with a strategy focused on innovation. As new technologies increase the ability to change sociotechnical levels, the changes that occur in the new window of opportunity do not change the landscape changes. Such changes involve regulatory and impacted models of how business owners manage data.